2019
DOI: 10.1186/s12916-019-1308-7
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of genotype-guided dosing of warfarin with point-of-care genetic testing in three UK clinics: a matched cohort study

Abstract: Background Warfarin is a widely used oral anticoagulant. Determining the correct dose required to maintain the international normalised ratio (INR) within a therapeutic range can be challenging. In a previous trial, we showed that a dosing algorithm incorporating point-of-care genotyping information (‘POCT-GGD’ approach) led to improved anticoagulation control. To determine whether this approach could translate into clinical practice, we undertook an implementation project using a matched cohort d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 26 publications
1
27
0
Order By: Relevance
“…EU-PACT provides an example of an international, multi-site trial which, due to its pragmatic approach and adoption of the biomarker-strategy design allowed the improved treatment outcomes from using a biomarker-guided approach to prescribing warfarin to be demonstrated. This has led to a subsequent matched-cohort study which demonstrated the successful implementation of the biomarker-guided approach into clinical practice [18], and a trial based on EU-PACT is currently being planned in Africa to test the clinical utility of a personalised approach to warfarin dosing in low-resource settings.…”
Section: Discussionmentioning
confidence: 99%
“…EU-PACT provides an example of an international, multi-site trial which, due to its pragmatic approach and adoption of the biomarker-strategy design allowed the improved treatment outcomes from using a biomarker-guided approach to prescribing warfarin to be demonstrated. This has led to a subsequent matched-cohort study which demonstrated the successful implementation of the biomarker-guided approach into clinical practice [18], and a trial based on EU-PACT is currently being planned in Africa to test the clinical utility of a personalised approach to warfarin dosing in low-resource settings.…”
Section: Discussionmentioning
confidence: 99%
“…Clinicians have used genotype information as a guideline to help determine the correct dose of warfarin. 35 The Clinical Pharmacogenetics Implementation Consortium published genotype-based drug guidelines to help clinicians optimize drug therapies with genetic test results. 36 Genomic profiling of tumors can inform targeted therapy plans for patients with breast or lung cancer.…”
Section: Precision Medicinementioning
confidence: 99%
“…Both CPIC [ 143 ] and DPWG have developed warfarin PGx guidelines for commencing warfarin that recommend validated genetic algorithms (e.g., the EU-PACT loading algorithm [ 15 ] or International Warfarin Pharmacogenetics Consortium (IWPC) algorithm [ 144 ]) or percent dose alterations. Importantly, point-of-care genotype-guided warfarin dosing has been shown to significantly improve TTR following implementation in real world anticoagulation clinics [ 145 ], and appears cost-effective [ 16 ].…”
Section: Warfarinmentioning
confidence: 99%